Two new species of the genus Anoplocheylus Berlese, 1910 (Acari: Trombidiformes: Pseudocheylidae) from Iran - Bagheri, Mohammad; Zarei, Elham; Ahaniazad, Mansoureh; Gharekhany, Gholamhossein; Navaei-Bonab, Reza (Zootaxa, 2013)
Two new species of the genus Anoplocheylus Berlese, 1910 (Acari: Trombidiformes: Pseudocheylidae), A. sinai Bagheri sp. nov. and A. kazemii Bagheri sp. nov., are described and figured. An updated key to all known species of Anoplocheylus is also provided.